Repercussões da pandemia de COVID-19 nas ocupações de crianças na primeira infância e de suas famílias - Pinheiro, Carolinne Linhares (Universidade Federal de São Carlos, 2026)
The COVID-19 pandemic was marked by restrictions and losses that threatened family and child well-being. This study analyzed the repercussions of the pandemic context on the occupations of young children and their families. An observational, longitudinal, qualitative–quantitative study was conducted with 126 caregivers of children in early childhood; 51 participants took part in both stages of data collection, which involved questionnaires and interviews. In Stage 1, changes experienced during the initial phase of the pandemic (IPP) were retrospectively examined in relation to children’s and caregivers’ occupations, participants’ stress levels, and child behavior. In Stage 2, post-pandemic, the study assessed the experience of returning to in-person schooling (RIP) and its effects on children’s occupations, as well as the pandemic’s impact on family economic conditions and parental work, participants’ stress, and child behavior, allowing for comparison with stage 1. Stress levels were measured using the Perceived Stress Scale–10, and child behavior was assessed using the Child Behavior Checklist (CBCL). Qualitative data were analyzed through thematic–categorical content analysis, while quantitative data were examined using descriptive and inferential statistics. The sample was predominantly composed of mothers (87.3%), most of whom belonged to higher socioeconomic strata (73%) and had higher educational attainment levels (68%). A deterioration in eating routines (51.6%) was identified, along with reduced sleep quality (43.6%) and duration (50%), decreased engagement in physical activity (54%), and a decline in both the diversity (65.9%) and frequency (75.4%) of caregivers’ leisure activities. Work-related changes—including remote work, income reduction, job loss, and increased workload—persisted throughout the pandemic period. Stress levels were significantly higher during the pandemic compared to the post-pandemic period (p < 0.001), largely due to disruptions in daily routines, such as managing work, household responsibilities, and childcare within a context of confinement and uncertainty. Many participants reported physical and emotional exhaustion and experiences of psychological distress. Parent–child relationships were negatively affected by continuous cohabitation and emotional dysregulation in both caregivers and children; however, some positive outcomes were noted, including strengthened family bonds. With respect to children’s occupations during the IPP, eating and sleep routines became more disorganized and less healthy. There was a reduction in physical activity (60.3%) and substantial spatial (66.7%) and social (48.4%) restrictions on play. Limitations on play opportunities and reduced parental availability for sustained engagement contributed to an increase in daily screen time (88.8%). Remote education posed an additional challenge for children and their families and appeared to be poorly aligned with the developmental needs of early childhood education. These changes were associated with notable impacts on child behavior. A significant increase in both internalizing and externalizing symptoms was observed (p < 0.001), as well as a higher proportion of children presenting scores indicative of difficulties across multiple CBCL subscales (p ≤ 0.012) during the pandemic compared to the pre-pandemic period. The RIP, in 2021 and 2022, yielded clear benefits for children’s occupational engagement. Participants reported reductions in screen time (92.7%), increased participation in physical activity (73.3%), greater engagement in play (73.2%), improvements in sleep (68.3%) and eating routines (41.5%), enhanced parent–child relationships (61%), and expanded social interaction, largely supported by the reestablishment of school routines. This study confirms the profound occupational disruption experienced by young children and their caregivers during periods of restrictive public health measures, with adverse consequences for family mental health. Over a prolonged period, children experienced reduced access to developmentally enriching and health-promoting opportunities, alongside increased exposure to habits and stimuli detrimental to health and well-being. The pandemic context thus appears to have functioned as a constraining force in early childhood development.
Repercussions of the COVID-19 pandemic on the occupations of young children and their families
Keywords: COVID-19; Distanciamento Físico; Saúde da Criança; Ocupações; Terapia Ocupacional; Physical Distancing; Child Health; Occupations; Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar